Sustainability in Global Trade: Integrating Principles for Inclusive and Resilient Systems - Lumempouw, Geysbert J (Universitas Diponegoro, 2024)
This paper examines the vital role of sustainability in global trade through a comprehensive literature review. It synthesizes existing research to explore the interplay between sustainability principles and international trade practices, focusing on environmental, social, and economic dimensions. Drawing from academic sources, the study analyzes the impact of sustainability standards on trade flows, the role of multinational corporations in promoting sustainable supply chains, and challenges and opportunities in mainstreaming sustainability in trade agreements. The findings underscore the necessity of integrating sustainability into trade policies and practices to foster inclusive, resilient, and environmentally sustainable global trade. Collaborative efforts among policymakers, businesses, and civil society stakeholders are essential to align trade objectives with sustainability goals and build a more sustainable future for global trade.